The Distinct Effects of Empathic Accuracy for a Romantic Partner's Appeasement and Dominance Emotions. (June 2020) - Le, Bonnie M.; Côté, Stéphane; Stellar, Jennifer; Impett, Emily A.
When is accurately reading other people's emotions costly and when is it beneficial? We aimed to identify whether the association between empathic accuracy and both relationship quality and motivation to change varies depending on the type of emotion being detected: appeasement (e.g., embarrassment) or dominance (e.g., anger). Romantic partners (couples: N = 111; individuals: N = 222) discussed a characteristic they wanted their partner to change and rated their own emotions and perceptions of their partner's emotions. Relationship quality was self-reported and objectively coded. Using multilevel response-surface analysis, we tested preregistered hypotheses about whether empathic accuracy for appeasement and dominance emotions was differentially associated with relationship quality and motivation to change. For appeasement emotions, empathic accuracy predicted higher relationship quality. For dominance emotions, higher intensity of felt emotions—not empathic accuracy—predicted lower relationship quality. Empathic accuracy did not predict the motivation to change. These results suggest that the benefits of empathic accuracy can depend on the emotion type.